All-Hex Meshing of Multiple-Region Domains without Cleanup. (2016) - Awad, Muhammad A.; Rushdi, Ahmad A.; Abbas, Misarah A.; Mitchell, Scott A.; Mahmoud, Ahmed H.; Bajaj, Chandrajit L.; Ebeida, Mohamed S.
Abstract: In this paper, we present a new algorithm for all-hex meshing of domains with multiple regions without post-processing cleanup. Our method starts with a strongly balanced octree. In contrast to snapping the grid points onto the geometric boundaries, we move points a slight distance away from the common boundaries. Then we intersect the moved grid with the geometry. This allows us to avoid creating any flat angles, and we are able to handle two-sided regions and more complex topologies than prior methods. The algorithm is robust and cleanup-free; without the use of any pillowing, swapping, or smoothing. Thus, our simple algorithm is also more predictable than prior art.